LOCAL WISDOM-BASED ENVIRONMENTAL COMMUNICATION IN ECOTOURISM PRESERVATION: A CASE STUDY OF THE INDIGENOUS COMMUNITY IN THE SAWARNA BEACH AREA - Muhammad Didi Ahmadi; Ade Taryana (Universitas Mercu Buana, 2026)
The threat of environmental damage due to massive tourism activities at Sawarna Beach has the potential to degrade coastal ecosystems, necessitating a communication pattern capable of integrating nature protection with the active involvement of the local community. This study aims to analyze and describe in depth how environmental communication strategies based on local wisdom values are implemented by indigenous communities in preserving Sawarna ecotourism. The researcher argues that the integration of local traditions into environmental information dissemination patterns is proven to strengthen tourists' ecological compliance and safeguard natural resources from the exploitation of mass tourism industries. Theoretically, this study applies Robert Cox’s concept of environmental communication alongside the theory of local wisdom to dissect message construction, communication channels, and cultural interactions in ecosystem management. The method used is a qualitative case study, with data collection techniques including in-depth interviews with customary leaders, field observations at Sawarna Beach, and documentary analysis of village regulations. Data analysis shows that the indigenous community utilizes interpersonal communication, customary rituals, and oral traditions as effective channels to internalize environmental preservation norms for both external parties and the local community. In conclusion, environmental communication based on local wisdom in Sawarna has successfully created a self-reliant, harmonious, and effective ecotourism preservation model to mitigate the negative impacts of environmental degradation in coastal areas.